FORMULASI SEDIAAN OBAT KUMUR EKSTRAK DAUN JARAK PAGAR (Jatropa curcus L) DENGAN KOMBINASI PENAMBAH PERASAN JERUK NIPIS (Citrus aurantifolis) SEBAGAI OBAT KUMUR ALAMI - sayyidah, sayyidah; Satria, Beny Maulana; Hasanah, Nur; Maelaningsih, Firdha Senja; Kristiyowati, Anis Dwi; dewi, Bheta sari; Rahajeng, Suny Koswara (PHRASE (Pharmaceutical Science) Journal, 2024)
*Corresponding Author SayyidahE-mail: sayyidah@wdh.ac.id Bad breath is a symptom of an unnoticed disorder or disease. However, sufferers have unpleasant bad breath that arises from the oral cavity. According to Regional Health Research (Riskesdes) in 2013 in the city of South Tangerang, dental and oral health problems increased from 2007 by 19.9% to 2014 by 34.2%, dental and oral problems in children aged 10-14 years were 20, 6%. Jatropha leaf extract can be formulated as a natural mouthwash. Mouthwash is one of the mouth preparations widely available on the market which can be used to treat bad breath, one of the causes of bad breath is the bacteria Candida albicans. Jatropha curcus (Jatropha curcus L) leaves are able to inhibit Candida albicans bacteria that cause bad breath. Lime also contains flavonoids which play a very important role in inhibiting bacterial growth. The aim of this research is to obtain the best physical preparation formula and to determine the evaluation of a mouthwash made from jatropha leaf extract (Jatropa curcus L) with a combination of lime juice (citus aurantifolia) as a natural mouthwash. The formulation of this preparation is made with variations of lime juice in FI (5%), FII (10%), and FIII (15%). The formulation of jatropha leaf extract mouthwash (Jatropha curcus L) was evaluated by physical tests including organoleptic, pH, clarity and viscosity tests. Jatropha curcus (Jatropha curcus L) mouthwash preparation meets pH, viscosity and organoleptic requirements. From the results of the research I conducted, the best preparation was FIII which had a glycerin concentration (15%) and then had a pH value at week 0: 5.91, week 1: 5.07, week 2: 5 .05 and has a viscosity value of 6.90 Cp, which means this viscosity meets the requirements, while the claritytest results obtained did not produce a clear formulation because the color of the Jatropha leafextract is dark green, so it affects the clarity of the formulation.